2008
DOI: 10.1186/1471-2202-9-75
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of edaravone-administration on 6-OHDA-treated dopaminergic neurons

Abstract: Background: Parkinson's disease (PD) is a neurological disorder characterized by the degeneration of nigrostriatal dopaminergic systems. Free radicals induced by oxidative stress are involved in the mechanisms of cell death in PD. This study clarifies the neuroprotective effects of edaravone (MCI-186, 3-methyl-1-phenyl-2-pyrazolin-5-one), which has already been used for the treatment of cerebral ischemia in Japan, on TH-positive dopaminergic neurons using PD model both in vitro and in vivo. 6-hydroxydopamine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…It has been used clinically to reduce neuronal damage resulting from cerebral ischemic stroke in Japan and China (Nakamura et al 2008). In addition, edaravone has displayed its protective effects in a variety of brain diseases, including traumatic brain injury (Ohta et al 2013), Alzheimer's disease (Yan et al 2012), and Parkinson's disease (Yuan et al 2008). Previous research has shown that edaravone plays an important role as a direct and indirect free radical scavenger by neutralizing toxic ROS and reactive nitrogen species (RNS) (Roh et al 2011).…”
mentioning
confidence: 99%
“…It has been used clinically to reduce neuronal damage resulting from cerebral ischemic stroke in Japan and China (Nakamura et al 2008). In addition, edaravone has displayed its protective effects in a variety of brain diseases, including traumatic brain injury (Ohta et al 2013), Alzheimer's disease (Yan et al 2012), and Parkinson's disease (Yuan et al 2008). Previous research has shown that edaravone plays an important role as a direct and indirect free radical scavenger by neutralizing toxic ROS and reactive nitrogen species (RNS) (Roh et al 2011).…”
mentioning
confidence: 99%
“…The areas were then calculated and used for statistical analyses. Accordingly to our previous publications (Yuan et al, 2008;Kikuchi et al, 2011), for counting the number of TH-positive neurons, every fifth 40μm-thick coronal tissue section through the substantia nigra pars compacta (SNc) was explored using 3 coronal sections respectively at 4.8 and 5.3 mm posterior to the bregma.…”
Section: Morphological Analysesmentioning
confidence: 99%
“…Studies regarding its incidence report that it is between 8 and 18 per 100,000 individuals per year (51). Edaravone was found to exert neuroprotective effects on PD models both in vivo (52) and in vitro (52,53). The underlying mechanisms may involve anti-apoptotic, anti-oxidative and/or the anti-inflammatory effects of edaravone (52,53).…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…Edaravone was found to exert neuroprotective effects on PD models both in vivo (52) and in vitro (52,53). The underlying mechanisms may involve anti-apoptotic, anti-oxidative and/or the anti-inflammatory effects of edaravone (52,53). Edaravone may be a potential therapeutic agent for PD, although the high therapeutic dosage required is a problem for clinical applications (52,53).…”
Section: Traumatic Brain Injurymentioning
confidence: 99%